2005
DOI: 10.1007/s10616-005-3776-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Immune Response in Peyer’s Patch Cells Induced by Oral Administration of Bifidobacterium Components

Abstract: We demonstrate immunomodulatory effects, especially those involving murine intestinal IgA secretion, in Peyer's patch cells following oral administration of Bifidobacterium immunomodulator (BIM) derived from sonicated B. pseudocatenulatum 7041. BALB/c mice were administered BIM orally for 7 consecutive days. The PP cells demonstrated upregulated secretion of total IgA including BIM-specific IgA following BIM administration. In observing the response of PP cells co-cultured with BIM, we found enhanced secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…We previously reported that oral administration of BIM induced IgA production by PP cells and cytokine production related to IgA production (e.g. IL-6 and IFN-c) by CD4 + cells derived from PP (Nakanishi et al 2005). It suggested that PP CD4 T cell might be activated to induce IgA production by oral administration of Bp components.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We previously reported that oral administration of BIM induced IgA production by PP cells and cytokine production related to IgA production (e.g. IL-6 and IFN-c) by CD4 + cells derived from PP (Nakanishi et al 2005). It suggested that PP CD4 T cell might be activated to induce IgA production by oral administration of Bp components.…”
Section: Discussionmentioning
confidence: 97%
“…Peyer's patch (PP) cells (2.5 9 10 5 cells mL -1 ) were obtained from 7-week-old female BALB/c mice, and cultured with each prepared Bp component (1 9 10 7 CFU) in RPMI 1640 medium containing 5% FCS in 96-well plates for 36 h. The proliferation activity of PP cells was measured by the [ 3 H]-thymidine uptake test according to a previously reported method (Hosono et al 1997 ) for 24 h. After co-cultivation, PP culture supernatant was obtained and IL-12p40 was measured by ELISA according to the previously reported methods (Hosono et al 1998;Nakanishi et al 2005).…”
Section: Proliferation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Bifidobacterium is a dominant genus of infants’ fecal flora that represent up to 90% of the total gut microflora in breast-fed babies [19] and up to 15% of that in adults [20]. Some strains of the genus Bifidobacterium exhibit anti-inflammatory properties [21,22,23], increase intestinal IgA secretion [24], and induce dendritic cell maturation [25]. …”
Section: Introductionmentioning
confidence: 99%